Advanced digital marketing strategies in a data-driven era - Saura, José Ramón, 1992- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2021)
"This book offers a holistic overview of the main applications and uses of data sciences in digital marketing strategies and business models, analyzing the new strategies that influence digital marketing and offering insights related to the creation of innovative data-driven and knowledge discovery techniques applied to traditional and digital marketing strategies"--